Optimization of Very Low-Dose Formulation of Vitamin D3 with Lyophilizate for Dry Powder Inhalation System by Simple Method Based on Time-of-Flight Theory - Kahori Miyamoto; Misato Yanagisawa; Hiroaki Taga; Hiromichi Yamaji; Tomomi Akita; Chikamasa Yamashita (MDPI AG, 2021)
It has been previously reported that active vitamin D3 (VD3) is a candidate drug that can repair alveolar damage in chronic obstructive pulmonary disease at a very low dose. We herein report the optimization of a very low-dose formulation of VD3 for dry powder inhalation by a simple method based on time-of-flight (TOF) theory. As the preparation content of VD3 is very low, aerodynamic particle size distribution cannot be measured by pharmacopeial methods that require quantification of the main drug. Thus, a simple method based on TOF theory, which can measure aerodynamic particle size distribution without quantification, was used. The optimized formulation for an inhalation system using a lyophilized cake contained phenylalanine as the excipient (VD3 1 μg/vial + phenylalanine 0.3 mg/vial) and showed high performance with fine particle fraction ≤ 3 μm = 47.2 ± 4.4%. The difference between the results of pharmacopeial methods and simple method was examined using the formulation containing 10 µg/vial of VD3 and was within 5.0%. The preparation is expected to efficiently deliver VD3 to the lungs. Our simple method can optimize dry powder inhalation formulations more easily and rapidly even when the content of the main drug in a preparation is very low.